Barriers and facilitators of deceased organ donation among Muslims living globally: protocol for an integrative systematic review using narrative synthesis - Gurch Randhawa; Erica Cook; Britzer Paul Vincent; Asmaa Al-Abdulghani; Riadh Fadhil (BMJ Open)
Introduction Muslims have been shown to have less favourable attitudes towards organ donation and are less likely to consent to donate their organs. While several studies have been undertaken globally to identify the barriers and facilitators of organ donation, no systematic review has synthesised this evidence to date. Therefore, this systematic review aims to identify the barriers and facilitators of organ donation among Muslims living globally.Methods and analysis This systematic review will include cross-sectional surveys and qualitative studies published between 30 April 2008 and 30 June 2023. Evidence will be restricted only to studies reported in English. An extensive search strategy will be used in PubMed, CINAHL, Medline, Scopus, PsycINFO, Global Health and Web of Science, as well as specific relevant journals that may not be indexed in these databases. A quality appraisal will be undertaken using Joanna Briggs Institute quality appraisal tool. An integrative narrative synthesis will be used to synthesise the evidence.Ethics and dissemination Ethical approval has been obtained from the Institute for Health Research Ethics Committee (IHREC) (IHREC987), University of Bedfordshire. The findings of this review will be disseminated widely through peer-reviewed journal articles and leading international conferences.PROSPERO registration number CRD42022345100.